Using ultrasonic technique to determine some petrophysical properties of core samples of Zubair and Mishrif Formations at Lu-5 and Tu-5 oil wells, southern Iraq - Khorshid, Salman; Salman, Rassoull (Iraqi Journal of Science, 2023)
Seventeen core samples were taken from Luhais and Tuba oil wells according to the presence of oil bearing formations. These wells were located in the province of Basra/southern Iraq. The formation that the samples are collected from Zubair and Mishrif formations. The core samples were taken from the wells at different depths. In the current study the ultrasonic technique was conducted to measure (Vp and Vs) as well as to determine some petrophysical properties for core samples and some elastic moduli such as (Young's modulus, Bulk modulus, Shear modulus, Poisson's ratio and Lame's constant) depending on the values of Vp and Vs as well as density. The relationships between seismic wave velocities with elastic moduli and petrophysical properties are plotted. Two core samples were selected from Lu-5 well core 4 to conduct laboratory measurements for porosity and compare it with the results of porosity which calculated from Vs.